2020
DOI: 10.1108/itse-07-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Construction and psychometric analysis of teachers mobile learning acceptance questionnaire

Abstract: Purpose The mobile technology-pedagogy nexus has been instrumental in shifting the focus of information and communications technology in education from e-learning to mobile learning (ML). Learning with mobile technologies is more accessible, flexible, situated, personal, collaborative and lifelong. The use of technologies for educational purposes is the primary focus of higher education institutes. The successful implementation of ML rests on its acceptance by higher education teachers. It is, therefore, perti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In this study, multiple intention-based models were adopted to explore university teachers’ beliefs about various aspects of the use of mobile technology-enhanced teaching (MTT) platforms. Among the theoretical intention-based models, the technology acceptance model (TAM) is the most used theoretical model for predicting and explaining users’ intentions to use mobile learning systems (Hsu, 2016 ; Lai et al, 2016 ; Mittal & Alavi, 2020 ), including teachers’ intentions (Beteille et al, 2020 ). In the TAM framework, perceived usefulness (PU) and perceived ease of use (PEU) are two key determinants of a particular technology adoption, such as mobile learning systems.…”
Section: Literature Review: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, multiple intention-based models were adopted to explore university teachers’ beliefs about various aspects of the use of mobile technology-enhanced teaching (MTT) platforms. Among the theoretical intention-based models, the technology acceptance model (TAM) is the most used theoretical model for predicting and explaining users’ intentions to use mobile learning systems (Hsu, 2016 ; Lai et al, 2016 ; Mittal & Alavi, 2020 ), including teachers’ intentions (Beteille et al, 2020 ). In the TAM framework, perceived usefulness (PU) and perceived ease of use (PEU) are two key determinants of a particular technology adoption, such as mobile learning systems.…”
Section: Literature Review: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Hsu ( 2016 ) used PU and PEU as the two determinants of mobile-assisted language learning use, while Lai et al ( 2016 ) adopted PEU as one predictive factor of high education teachers’ mobile learning environment use. Recently, Mittal and Alavi ( 2020 ) found that both PU and PEU were significant factors in the context of university teachers’ mobile learning acceptance.…”
Section: Literature Review: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The use of the m-learning method in education has been growing in recent years (MITTAL;ALAVI, 2020). This can be understood as the training process, which is carried out from any place and at any time, thanks to the use of mobile terminals with a wireless connection, which allows students to access the necessary data, either through the network or in documentation stored in the device (AL-EMRAN et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ain Nadzimah Abdullah and Arshad Abdul Samad are with the School of Education, Taylor's University, Subang Jaya, Selangor, Malaysia (e-mail: ainnadzimah.abdullah@taylors.edu.my, arshad.abdsamad@taylors.edu.my). environment (p. 171) [5]." Later, the notion of Mobile-Assisted Language Learning (MALL) was proposed as a subset of Computer-Assisted Language Learning (CALL) and m-learning.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (such as Ozdamli & Uzunboylu [9]; Liu, Tao & Cain [10]) argued that while most college language learners had positive attitudes towards MALL, many language teachers were undecided, apprehensive, and had misgivings about it. Researchers, Mittal and Alavi [5], have suggested that the successful implementation of MALL for language education relies heavily on EFL teachers and their acceptance. However, Chen and Jia [11] in their review of studies conducted in China disclosed that they tended to focus on students whereas studies on in-service EFL teachers' perceptions and acceptance of the use of MALL have been neglected.…”
Section: Introductionmentioning
confidence: 99%